New treatment options for thrombotic thrombocytopenic purpura - Knöbl, Paul (Hämostaseologie, 2017)
The thrombotic-thrombocytopenic purpura (TTP) is an acute, life-threatening disease, characterised by enhanced platelet aggregation, disturbed microcirculation and organ dysfunction. With the currently available treatment (plasma exchange, infusions, corticosteroids) mortality ist still as high as 10–15 %. Recent, pathophysiology-based developments may improve the outcome. The most promising candidates for future treatment of TTP are: rituximab for termination of the autoimmune process, caplacizumab for prevention of platelet-VWF-interaction, and recombinant ADAMTS13 for replacement of the inhibited or missing enzyme.
Keywords: Thrombotic-thrombocytopenic purpura; ADAMTS13; von Willebrand factor; therapy